VD_FINDINFO HC / 2013 / 44 vom 23. November 2012 - VD Tribunal cantonal (2012)
SUSPENSION DU DÉLAI, FÉRIES JUDICIAIRES, ACTE DE NON-CONCILIATION, DÉLAI LÉGAL | 145 al. 1 CPC (CH), 209 al. 3 CPC (CH), 209 al. 4 CPC (CH), 308 al. 1 let. a CPC (CH), 308 al. 2 CPC (CH)